Lateral epicondylalgia: A primary nervous system disorder. (February 2019) - Bordachar, Diego
Abstract: Lateral epicondylalgia (LE) is the most common chronic painful condition affecting the elbow in the general population. Although major advances have been accomplished in recent years in the understanding of LE, the underlying physiopathology is still a reason for debate. Differences in clinical presentation and evolution of the symptoms among patients, suggest the need for revisiting the current knowledge about subjacent mechanisms that attempt to explain pain and functional loss. Previous models have suggested that the condition is mainly a degenerative tendinopathy, associated with changes in pain pathways and the motor system. The hypothesis of this work is that LE is the clinical manifestation of a primary nervous system disorder, characterized by an abnormal increase in neuronal activity and a subsequent loss of homeostasis, which secondarily affects the musculoskeletal tissues of the elbow-forearm-hand complex. A new model for LE is presented, supported by an in-deep analysis of basic sciences, epidemiological and clinical studies.